Endogenous credibility and wage-price spirals - Olena Kostyshyna; Tolga Özden; Yang Zhang (Bank of Canada, 2024)
Elevated inflation can threaten the credibility of central banks and increase the risk that inflation expectations do not remain anchored. Wage-price spirals might develop in such an environment, and high inflation could become entrenched. We quantitively assess the risks of a wage-price spiral occurring in Canada over history by using a medium-scale dynamic stochastic general equilibrium model enhanced with heterogenous expectation and learning. This mechanism generates time-varying propagation of inflationary shocks that improves forecasting performance of inflation and wage growth. Central bank credibility is endogenous in our model and depends on several notions of the learning mechanism. Weaker credibility and a higher risk of inflation expectations not remaining anchored increase the risk of a wage-price spiral.
Keywords: E00; E7; E47; C22; 330; Business fluctuations and cycles; Credibility; Inflation and prices; Monetary policy